2018
DOI: 10.3389/fimmu.2018.02192
|View full text |Cite
|
Sign up to set email alerts
|

HFA-BDP Metered-Dose Inhaler Exhaled Through the Nose Improves Eosinophilic Chronic Rhinosinusitis With Bronchial Asthma: A Blinded, Placebo-Controlled Study

Abstract: Background: Eosinophilic chronic rhinosinusitis (ECRS) is a subtype of chronic rhinosinusitis with nasal polyps in Japanese. ECRS highly associated with asthma is a refractory eosinophilic airway inflammation and requires comprehensive care as part of the united airway concept. We recently reported a series of ECRS patients with asthma treated with fine-particle inhaled corticosteroid (ICS) exhalation through the nose (ETN).Objective: To evaluate fine-particle ICS ETN treatment as a potential therapeutic optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In addition to improvements in the above outcomes, RWE studies reported that non-biologics improved SNOT-22 scores, Lund-Kennedy CT and endoscopic scores, total symptom scores by VAS, and nasal polyp scores (Supplementary Tables 5, 7 , 9, 11, 13, and 14). Four RCTs [77][78][79][80] and 4 RWE studies [81][82][83][84] reported on non-biologics (corticosteroids and ESS) for patients with eCRSwNP. All eight studies demonstrated improvement in clinical outcomes.…”
Section: Results For Non-biologicsmentioning
confidence: 99%
“…In addition to improvements in the above outcomes, RWE studies reported that non-biologics improved SNOT-22 scores, Lund-Kennedy CT and endoscopic scores, total symptom scores by VAS, and nasal polyp scores (Supplementary Tables 5, 7 , 9, 11, 13, and 14). Four RCTs [77][78][79][80] and 4 RWE studies [81][82][83][84] reported on non-biologics (corticosteroids and ESS) for patients with eCRSwNP. All eight studies demonstrated improvement in clinical outcomes.…”
Section: Results For Non-biologicsmentioning
confidence: 99%
“…Ten RCTs [14][15][16][17][18][19][20][21][22][23] and 42 RWE studies reported mean or median baseline SNOT-22 scores for study populations consisting of surgical candidates. In all studies, baseline SNOT-22 score was assessed prior to surgical interventions.…”
Section: Disease-specific Health-related Quality Of Lifementioning
confidence: 99%
“…Of the 10 RCTs 14-23 and 42 RWE studies reporting baseline SNOT-22 scores for surgical candidates, all ranged from moderate to severe (Table 4) 91 . Five RCTs [14][15][16][17][18] and 25 RWE studies 65 reported mean baseline SNOT-22 scores in the moderate range. Five RCTs [19][20][21][22][23] and 17 RWE studies [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] reported severe mean baseline SNOT-22 scores.…”
Section: Stratification Of Snot-22 Scores Prior To Surgerymentioning
confidence: 99%
“…A second ESS was performed for his refractory ECRS. In addition, inhaled corticosteroid (ICS) exhalation through the nose (ETN) treatment, which provides better control for both asthma and nasal symptoms, 5,6 was initiated instead of conventional ICS exhalation through the mouth treatment. To prevent recurrence of ECRS and reduce asthma symptoms, the doses of ICS were increased to up to 1800 mg. Thirty months after the second ESS, cholecystitis occurred concomitantly with the recurrence of nasal polyps while the doses of ICS were decreased to 1400 mg, 2 months before the onset of biliary colic.…”
Section: Case Presentationmentioning
confidence: 99%